Penggunaan Uji Konduktivitas Sebagai Uji Vigor Pada Benih Gandum (Triticum aestivum L.) - Endang Murwantini; Aswaldi Anwar; Nalwida Rozen (Program Studi Agroteknologi Fakultas Pertanian Universitas Andalas, 2018)
Conductivity test is a test to physically measure the electrolyte leaking from seeds and be classified as vigor test. However, some factors may affect the result of the test; therefore, standardized procedures should be defined for its accuracy and consistency. The research reported here was aimed at obtaining specific method of conductivity test for wheat seeds and to study the correlation between conductivity test result with seed germination and field emergence. The experiments were conducted at the laboratory of BBPPMBTPH, Cimanggis, Depok from February to June 2013. The experiment was designed to identify the correct amount of wheat seeds and the volume of water used to soak the seeds. The experiment was assigned according to a completely randomized design (CRD) with 20 wheat seed lots and three replicates. Data collected including seed germination (SG), vigor index (IV) or First Count Test (FCT), field emergence (FE) at 8, 14, and 21 days, tetrazolium test (TZ), and conductivity test for nine combinations of wheat seed amount and the water volume for soaking (50, 75, and 100 seeds in 100, 150, and 200 mL of water). Results show that soaking 75 wheat seeds in 200 mL of water was best for conductivity test. This soaking condition resulted in negatively significant correlation between seed germination and field emergence. Moreover, low value of conductivity resulted in high values of SG, IV, FE, and TZ. Wheat seed germination and field emergence can be estimated using the equations of y = 0.028x2 – 3.321x + 104.9 and y = 0.022x2 – 2.704x + 87.96, respectively.